Gender, sexuality, and peace education : issues and perspectives in higher education - Finley, Laura L. (Peace education., 2018)
This edited volume, authored by scholars, students, and activists, focuses on how peace educators at the collegiate level can more effectively address gender and sexuality. Chapters focus on the classroom and the campus at large, and emphasize the importance of interdisciplinary practice, thoughtful approaches that offer both challenges and safety, and solidarity and support. The volume includes entries on hot and important topics, including trigger warnings, using popular culture in the classroom, sex trafficking, campus sexual assault, and more. Contributors come from a variety of disciplinary areas, making the volume eclectic in nature. Further, most entries include student voices, providing much- needed agency for college youth. While the book does offer a critical perspective, importantly, chapters also offer hope and possibility.